Assemblages for community-led social housing regeneration: Activism, Big Society and localism. Issue 5 (2nd November 2018) - Sendra, Pablo
Abstract : This paper connects two debates previously featured in City : 'Assemblage and Critical Urban Praxis' and 'London's Housing Crisis and its Activism'. The paper uses assemblage thinking to explore how community organisations and campaigns in London use a combination of different tools, which engage with the planning system and other actions or strategies outside planning, to resist council estate demolition and propose alternative community-led plans incorporating the needs and wishes of residents. The paper first looks at the planning tools available in the English Localism Act 2011 for involving residents in decision-making processes, examining their limitations when being used to oppose council estate demolition while proposing alternative plans. Four case studies of campaigns and community organisations—Greater Carpenters Neighbourhood Forum, Focus E15, Save Cressingham, and West Ken and Gibbs Green Community Homes—are then used to explore how they have generated three kinds of assemblages which create capabilities for self-organisation, resisting demolition, and influencing decision-making processes. The first kind of assemblage combines formal and informal strategies—some engaging with the planning system and some not; the second uses both formal and informal organisations based on the desired objectives and the nature of their actions; and finally, the third builds support networks with professionals and other initiatives.